International education policy : its influence on the conception of VET and the VET system in Germany - Deissinger, Thomas [Verfasser] (My University, 2015)
"Inquiries into vocational education and training (VET) systems are normally characterised by looking at institutions and steering mechanisms. That aside, however, it is culture which underlies both the practice and the theory as well as the policy of VET in various countries. Specific problems arise when it comes to harmonising VET systems through the backdoor. One of the current supranational instruments in this context is the European qualifications framework (EQF) and other related instruments as well as OECD expectations referring to increasing the numbers of higher education graduates. The PISA studies certainly also play their part within these influential streams of international education policy, in so far as they put pressure on school systems to change, depending on the performance of students. The PISA findings are then generalised by rebuking whole education systems as well as pointing to best practice countries like Finland. In contrast to PISA, though, the EQF is not as well-known an instrument outside the world of education, although its long-term impact should not be underestimated as it could result in specific national reform steps beyond the issue of raising the quality of school education. In this respect, its implications may be compared to those deriving from OECD studies rebuking countries once they fail to increase progression to and participation in higher education, since this issue touches the basic architecture of the whole education system and its underlying cultural and pedagogical paradigms. Since Germany is a typical example of an 'apprenticeship country', the paper picks up these immanent matching problems by referring to the German institutional framework of VET, including forms and practices of non-state intervention into the system and, in particular, to the responsibility of non-state institutions such as the social partners, who have specific views on preserving the culture behind the dual system in the context of internationalisation. The paper also touches on other specific issues associated with Europeanisation of VET, i.e. the function of hybrid qualifications, which are quite common in the UK or France, but also in Switzerland with its traditional apprenticeship system. They refer to the dimension of lifelong learning policy in so far as they touch the relationship between VET and higher education, but also the basic question of new progression routes within the education system." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S System beruflicher Bildung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 4.3 Steuerung; I 2.1 Deutschland; I 2.2 Europa; EU-Bildungspolitik; Europäische Integration; Berufsbildungssystem; Berufsbildungspolitik; Europäischer Qualifikationsrahmen; Bildungssteuerung; Bundesrepublik Deutschland